The immune system - Parham, P. [ (Peter)] , 1950-; Janeway, Charles A. (Garland Science, 2009)
Focuses on the human immune system and synthesizes immunological concepts into a comprehensible and reader-friendly account of how the immune system works. Written for undergraduate, medical, veterinary, dental, and pharmacy students in immunology courses, this work makes use of medical examples to illustrate points.